Crédito bancario al sector privado y crecimiento económico en México: Un análisis con datos panel por entidad federativa 2005-2018 - Leonardo Egidio Torre Cepeda; Miguel A. Flores Segovia (Banco de México, 2020)
– The paper investigates the effect of banking credit to private agriculture, industrial and services sectors, on per capita GDP growth in Mexico using panel data at the state level for the period 2005-2018. The estimation controls for variables related to infrastructure, public expenditure, exports, inflation, human capital, a dummy for the 2008-2009 global financial crisis, and introduces a lag of the dependent variable in order to consider its likely persistence. Using the Generalized Method of Moments in order to control for possible endogenous effects among the variables, it is estimated that a 10% increase in the ratio of banking credit to GDP increases per capita GDP growth at the state level between 0.61 and 0.81 percentage points. These results underline the relevance of policy measures designed to promote a healthy functioning of the financial system in Mexico.
Keywords: O47; G21; R11; R15; 330; Banking Credit; Economic Growth; Regional Analysis; Mexico